1993
DOI: 10.1161/01.str.24.12.1794
|View full text |Cite
|
Sign up to set email alerts
|

Predicting length of stay, functional outcome, and aftercare in the rehabilitation of stroke patients. The dominant role of higher-order cognition.

Abstract: The need is discussed for early, comprehensive assessment of deficits in cognition that affect a stroke survivor's ability to participate in a rehabilitation program and remediation that facilitates functional improvement by building on residuals of impaired abilities or teaching compensatory behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 35 publications
3
76
1
1
Order By: Relevance
“…While previous studies have demonstrated that a cognitive deterioration within the first three months post-stroke is a good predictor of an adverse functional outcome (Galski et al, 1993;Tatemichi et al, 1994;Mok et al, 2004;Nys et al, 2005) and post-stroke dementia (Lin et al, 2003), it is not known whether a detailed evaluation of specific cognitive functions in the early phase of stroke can give valid information about domain-specific cognitive functioning in the long term. Moreover, the prevalence of cognitive recovery and the cognitive abilities most likely to recover have not been adequately investigated, and it is unclear which clinical factors influence cognitive recovery after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have demonstrated that a cognitive deterioration within the first three months post-stroke is a good predictor of an adverse functional outcome (Galski et al, 1993;Tatemichi et al, 1994;Mok et al, 2004;Nys et al, 2005) and post-stroke dementia (Lin et al, 2003), it is not known whether a detailed evaluation of specific cognitive functions in the early phase of stroke can give valid information about domain-specific cognitive functioning in the long term. Moreover, the prevalence of cognitive recovery and the cognitive abilities most likely to recover have not been adequately investigated, and it is unclear which clinical factors influence cognitive recovery after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Fizioterapeuti i medicinske sestre s odjela interne klinike i odjela rehabilitacije veći-nom smatraju (56,8 %) kako rade u interdisciplinarnom timu, uz pokazatelj znatno bolje otvorene komunikacije na odjelu rehabilitacije 18 . Timska suradnja interdisciplinarnog tipa u rehabilitaciji primjere dobre kliničke prakse prikazuje kod neuromuskularnih bolesti 6 , ortopedije 19 , ortotike 20 i protetike 3 , fizikalne medicine i rehabiltacije 21 i cerebrovaskularnih bolesti 22 , no budući da u većini dostupne literature odnosi između članova tima nisu točno specificirani 13 , a imaju elemente interdisciplinarnosti, možemo smatrati da postoje dokazi o prihvaćenosti pristupa i u drugim područjima.…”
Section: Izazov U Struci I Organizaciji Rehabilitacijske Skrbiunclassified
“…8,9 Moreover, most of these studies have used global cognitive screening measures in the early phase of stroke, although these measures demonstrate poor sensitivity in detecting cognitive impairment in stroke patients.…”
Section: Abstract-objectivementioning
confidence: 99%
“…[1][2][3][4][5] While cognitive disorders are among the most frequent and devastating early consequences of stroke, 6,7 few studies have examined the prognostic importance of these acute disorders. 8,9 Moreover, most of these studies have used global cognitive screening measures in the early phase of stroke, although these measures demonstrate poor sensitivity in detecting cognitive impairment in stroke patients. 10 Also, these global measures do not allow evaluation of cognitive performance in specific domains.…”
mentioning
confidence: 99%